PERANCANGAN JEMBATAN GANTUNG PEJALAN KAKI KELAS I DENGAN BENTANG UTAMA 2x80 METER - , ASTRIANA HARDAWATI; , Dr. -Ing. Ir. Djoko Sulistyo. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Human always move and often meet some obstacles, like river. Bridge is a structure that can be the solution to move through the river. There are some manual books about bridge design provide dimensions and steelprofiles for one span suspension bridge for pedestrian. Suspension bridge is well known as long span bridge because it can be built without pylon in the middle of span. In some cases, there are some typical rivers whose half-side is always dry at dry season so it is possible to build pylon in the middle of span and make two spans suspension bridge. By making two spans, it can minimize the size of structural steel profiles. Therefore, it can be more efficient and more comfortable. This design of suspension pedestrian bridge 2x80 m aimed to design the main shape and dimension of bridge including load analysis, structural analysis, design bridge elements, and deformation analysis. This design is preceded by modeling the bridge in SAP2000 software and determined load design with load combinations that will work in bridge to obtain response structure. Then the result is used to design the dimension of bridge elements that fulfill strength and serviceability requirements. Structural modeling for cable support at the top edge of center pylon is generated as fixed support while the supports at the edge pylons are modeled as roll support. The support for lateral girder above the foundation of center pylon is modeled as hinge support, while the lateral girder above the foundation of edge pylons is modeled as roll support. Results obtained from the design are: for longitudinal beam use IWF 150.100.5.7, for transverse beam use 2C-150.75.6.5.11, for diagonal beam use L- 70.70.7, for side pylon use IWF 300.200.9.4, for mid pylon use IWF 400.400.30.50, for main cable use 6x37 FC with 60 mm diameter, for hanger use 6x37 FC with 16 mm diameter, for wind bracing use 6x37 FC with 10 mm diameter. For bridge sub structure stone masonry foundations are used, with dimesion of 2.5 m x3 m for side pylon and 4.5 m x 6.5 m for middle pylon, and each with 3 m in depth. Anchor blocks have dimension of 2.5 m x7 m and safety factor of 2.482 against overturning and safety factor of 1.645 against sliding. Maximum deformation is resulted from asymmetric load with magnitude of 0.740 m in the middle of span.